Crafting People Descriptions: A Case Study of Student Public Speaking in a Non-English Department - Pipit Rahayu; Eripuddin Eripuddin (STAI Hubbulwathan Duri, 2023)
The abilities of students’ public speaking are different at some level. This study investigates the students’ speaking skills in describing people in the Non-English Department. The type of this research was a quantitative descriptive study design. The instrument of this study was the test; the type of the test was public speaking in describing people. The population of this study was 37 students in the 2nd semester of sports and health education. The sampling technique was total sampling. The sample was 37 students. Primarily based on the result, the researcher discovered that one student (2%) has a good score, 17 students (46%) have an average rating, and 19 college students (51%) have a fair rating. It means that the score of students' speaking skills in describing humans became a truthful stage. It brought about mispronunciation of phrases (body, eyes, nose, and colour), messy grammar, lack of vocabulary, fluency gradual, and comprehension most effective a little and quite simple.